IMPROVING STUDENTS’ SKILL IN WRITING HORTATORY EXPOSITION THROUGH EMPHASIZING GUIDANCE IN PRE-WRITING STAGE - Rozi, Fahrur; Husin, Syarif; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: Permasalahansiswadalammenulisadalahmerekatidaktahubagaimanacaramenemukan ide danmengembangkan ide tersebutuntuktulisanmerekadanbagaimanamenggunakanpendapatmerekaterhadapsebuah ide tersebut. Untukmembantusiswadalammemecahkanpermasalahantersebut, penulismenggunakanteknikpenekananbimbingandalamtahappra-menulisdenganmemberikanmerekapertanyaan-pertanyaanterkaitdenganteks model yang telahdisiapkanuntukmembantusiswamenemukan ide untuktulisanmereka.Untukmembantumerekamenggunakanpendapatmerekasendiri di dalamtulisnmereka, penulismemilihteksberbentuk hortatory exposition.Penelitianinidilakukandenganmetode pre-experimental desainsatukelompok pretest-posttest yang bertujuanuntukmengetahuiapakahpenekananbimbingan  yang menggunakanpertanyaan 5WH dapatmeningkatkankemampuansiswakelassebelas di SMA Negeri 6 tahunakademik 2012/2013 dalammenulisteksberbentuk hortatory exposition. Kelas yang dipiliholehpenulisadalahkelas IPA A yang terdiridari 27 siswa.Teknikpengumpulan data yang digunakanadalahpengukurandanalat yang digunakanuntukmengumpulkan data adalahtestertulis.Penelitianinimenunjukkanbahwapenekananbimbingandenganmenggunakan 5WH dalamtahappra-menulisefektifdalammeningkatkankemampuansiswadalammenulisteksberbentuk hortatory exposition.Hasildarianalisis data menunjukkanpeningkatan yang signifikansebesar 21.85 dengannilai rata-rata pretest yaitu 55.19 yang tergolongdalamkriterianilai rata-rata dannilai rata-rata posttest yaitu 77.05 yang tergolongdalamkriterianilaibaik. Efekpengukurandariperlakuanmenunjukkanbahwapenekananbimbingandenganmenggunakanpertanyaan 5WH dalamtahappra-menulissangatefektifdalammeningkatkankemampuansiswadalammenulisteksberbentuk hortatory exposition.   Kata Kunci: PenekananBimbinganPadaTahapPra-Menulis, TeksBerbentuk Hortatory Exposition Abstract: Most of students’ problems in writing are that they do not know how to generate and develop the idea for their writing and how to express their opinion of an idea. To help the students to overcome their problems, the writer used emphasizing guidance technique in prewriting stage by giving the students 5WH questions provided by the writer to help the students to generate the idea for their writing. To help them to use their own opinion of an idea in their writing, the writer chose hortatory exposition text.This research was conducted in a pre-experimental one group pretest-posttest design and purposed to investigate whether the emphasis of guidance by using 5WH questions can improve students’ skill in writing hortatory exposition text to eleventh grade students of SMA Negeri 6 Pontianak in academic year 2012/2013. The class which was taken by the writer was science class A which consists of 27 students. The technique of data collecting was measurement and the tool of data collecting was written test.It was found that emphasizing guidance by using 5WH in prewriting stage is effective in improving students’ skill in writing hortatory exposition text. The result of data analysis showed significant improvement of 21.85 with mean score of pretest 55.19 which is qualified as average and mean score of posttest 77.05 which is qualified as good. The effect size of the treatment (1.91) is more than 0.8 and categorized as high. The effect size of treatment shows that emphasizing guidance by using 5WH questions in prewriting stage is highly effective in improving students’ skill in writing hortatory exposition text.   Keywords: Emphasizing Guidance in Pre-Writing stage, Hortatory Exposition Text